The Association between Childhood Overweight and Reflux Esophagitis - Nirav R. Patel; Mary J. Ward; Debra Beneck; Susanna Cunningham-Rundles; Aeri Moon (Journal of Obesity)
Background. In adults, it has been shown that obesity is associated with gastroesophageal reflux disease (GERD) and GERD-related complications. There are sparse pediatric data demonstrating associations between childhood overweight and GERD. Objective. To investigate the association between childhood overweight and RE. Methods. We performed a retrospective chart review of 230 children (M : F=114 : 116) who underwent esophagogastroduodenoscopy (EGD) with biopsies between January 2000 and April 2006. Patient demographics, weight, height, clinical indications for the procedure, the prevalence of BMI classification groups, the prevalence of RE and usage of anti-reflux medications were reviewed. For these analyses, the overweight group was defined to include subjects with BMI≥ 85th percentile. The normal weight group was defined to include subjects with BMI 5th to 85th percentile. Results. Among the 230 subjects, 67 (29.1%) had BMI percentiles above the 85th percentile for age and gender. The prevalence of RE in the overweight group did not differ significantly from that in the normal weight group (23.9% versus 24.5%, resp.). Overweight subjects taking anti-reflux medications clearly demonstrated a higher prevalence of biopsy-proven RE compared to overweight subjects not taking anti-reflux medications (34.1% versus 7.7%, 𝑃=.009). Conclusions. There was no significant difference in the prevalence of biopsy-proven RE in the overweight group compared to the normal weight group. However, the prevalence of RE was significantly higher in overweight subjects on anti-reflux medications compared to overweight subjects not taking anti-reflux medications. This finding emphasizes the importance of early recognition and treatment of GERD for the overweight pediatric patients with symptoms in conjunction with weight loss program for this population to reduce long-term morbidities associated with GERD.